CRYPTOGRAPHIC TECHNOLOGIES AND THEIR IMPACT ON THE DEVELOPMENT OF INVESTMENT SERVICES IN UKRAINE - Oleksii Dotsenko; Yelyzaveta Pushyna (Соціальна економіка)
In today’s rapidly evolving technological world, cryptographic technologies, including blockchain and smart contracts, significantly impact various sectors of the economy, including investment services. This article explores the impact of cryptographic technologies on the investment services market in Ukraine, analyzing international experiences and potential applications in the Ukrainian context.